Perceptions and experiences of students on the use of interactive online learning technologies in Mauritius - Parmeswar Ramkissoon; Louis Jinot Belle; Trishnee Bhurosy (Institute of Advanced Engineering and Science, 2020)
With the advent of e-learning, advocates use the term interactivity instead of interaction among students, and between the teacher and the students. Many universities use Moodle for online teaching and learning. This paper explores the perceptions and experiences of students in three Higher Education Institutions (HEIs) in Mauritius. A mixed-methods approach was used, with an online survey questionnaire administered to 600 students and focus group discussions were conducted with 15 students from these institutions. It was found that 68.4% of respondents used WhatsApp compared to only 23.6% of them who used the e-learning platform, Moodle. There were no associations between the use or frequency of using WhatsApp or Facebook and the types of HEI to which the students belonged. Students preferred WhatsApp due to its facility for knowledge sharing and construction, its interactivity, its usability, respect for privacy and instant communication. From the findings, it is recommended that HEIs bring a shift in their approaches to teaching and learning from cognitivism to socio-constructivism, connectivism and heutagogy.